Industrial Training Report: Perpustakaan Negara Malaysia / Siti Fatimah Tomas - Tomas, Siti Fatimah (Faculty of Information Management, 2018)
This professional training report was done as one of the requirement when the trainee staff completed her attachment with the industry/organization. The report explain on the activities done by the trainee staff during her (5) five months attachment from I st August 2018 until 31st December 2018. Trainee staff is a lecturer from Faculty of Information Management, UiTM Negeri Sembilan, Rembau Campus. The professional training was done at National Library of Malaysia (PNM) by focusing in four (4) division/department. These four department is Sahagian Pembangunan Modal lnsan (SPMI), Sahagian Penyelidikan Perpustakaan (BPP), Pusat Sibliografi Negara (PBN) dan Sahagian Pinjaman (SPMJ). These division were requested by the trainee staff as they provide skills needed by the trainee staff. Furthermore, by going for an attachment at national library, trainee staff learned and gained a lot of information and knowledge that can be applied in her teaching task in the future.